If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + 4(-7 + 2g) = 1 + -1g 4g + (-7 * 4 + 2g * 4) = 1 + -1g 4g + (-28 + 8g) = 1 + -1g Reorder the terms: -28 + 4g + 8g = 1 + -1g Combine like terms: 4g + 8g = 12g -28 + 12g = 1 + -1g Solving -28 + 12g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -28 + 12g + g = 1 + -1g + g Combine like terms: 12g + g = 13g -28 + 13g = 1 + -1g + g Combine like terms: -1g + g = 0 -28 + 13g = 1 + 0 -28 + 13g = 1 Add '28' to each side of the equation. -28 + 28 + 13g = 1 + 28 Combine like terms: -28 + 28 = 0 0 + 13g = 1 + 28 13g = 1 + 28 Combine like terms: 1 + 28 = 29 13g = 29 Divide each side by '13'. g = 2.230769231 Simplifying g = 2.230769231
| 3x*3x-6x+1=0 | | 7m-5(1+m)=5 | | -38=-6x+4(4x+3) | | 1413.7=360x | | 2(x-2)=-4(x-2) | | 82=2x-4(-6x+12) | | 3-5b+7-2b= | | 3x(x)+12=0 | | 11+4q=13+3q | | -5x-2(-6x+6)=58 | | 6x*3w= | | 8x+10y=80 | | 90*47=360x | | -3/4x=24 | | 90*31.41=360x | | 7=w/17.5 | | (2x^2)(3x^2)= | | a(bx+3)=cx-6 | | -34x=24 | | 4.3x+2=3.3x | | 6(4-y)=12 | | 2x^4+4x^3-2x-1=0 | | x+x+x=x | | -3(x+4)+6=7(x+3)+4 | | 3(x+2)-4=12 | | 2+2=6a | | 4-a*-1/2 | | 4-a/-1/2 | | 8.5+1.1*100-9.3/0.2 | | 6(4y-3)-(7y+5)= | | x=3/4x+8 | | p+18=-32 |